A Commentary on Perceived Need from Indian Perspective - Joshi, Ankur; Kale, Saket; Phadnis, Sameer (Indian Journal of Community Health, 2016)
The current Indian health –care scenario is overwhelmed not only with burden of diseases but also with quality of care and expenditures. The structure of this paper is interwoven around a storyline about a patient and narrations of the active actors involved in the journey of illness including patient himself. The narrations are followed by a commentary as an attempt to decipher the deeper meaning of narration from the population perspectives. The essential aim of this exercise is to establish the necessity of generalist care from a qualitative view-point in Indian context.